GE_GERICHTE P/4056/2016 vom 10. Januar 2018 - GE Cour de justice (2018)
ARME(OBJET) ; EXPORTATION(EN GÉNÉRAL) ; ERREUR SUR LES FAITS(DROIT PÉNAL) | LCB.14.al3.ch2.par3; CP.13; CP.21; CP.47; CPP.429.al1; LArm.4.al1.leta; LArm.22.al1; CBA.3.al1; OCB.13.al1